PLS-SEM Model of Leadership Characteristics facing Challenges in Malaysia Construction Industry - Ain Ngah Nasaruddin, Nur; Abdul Rahman, Ismail; Musa Jaber, Mustafa (International Journal of Engineering and Technology, 2018)
Ensuring successful completion of construction projects within the stipulated time, cost and quality; there are many challenges need to be addressed by construction leadership’s team.  In addressing these challenges, the team members should possess relevant leadership characteristics. Hence, this paper presents a development of PLS-SEM model on the relationship between the required leadership characteristics with the related construction’s challenges. This model was generated using Smart PLS-SEM software based on questionnaire survey data from 50 valid responses. The data consisted of 43 leadership characteristics which are clustered in 5 groups and 9 construction’s challenges clustered in 1 group. The developed model indicated that Constructive Relationship (CR) group is the most influential group with strength of impact path (β) value of 0.451 in dealing the construction challenges with Genuine with subordinates as the most influential leadership characteristic. While, Quality is the most challenges item in construction challenges group. The model is beneficial to the industry community in facing dynamism of the construction challenges ahead.